Doing Away with "Database:" Exploring Medical Library Website Design. Issue 3 (1st October 2020) - Cirelli, Marie C.; Long, Bradley A.
Abstract: Library users can become confused by library jargon, especially the term "databases." This study utilized a combination of end-user surveys and library website usability testing to determine if library users at an academic health sciences library were, in fact, using different terminology to refer to the library's database collection. This study was devised to probe students' information needs and nomenclature for library resources and identify different ways of organizing information on the library's website outside of the traditional database page and "Quick Links." The study yielded valuable insight into how our users are identifying information resources that will allow us to improve website usability.